DNA Delivery for Vaccination and Therapeutics Through the Skin - Foldvari, Marianna; Babiuk, Shawn; Badea, Ildiko (Current Drug Delivery, 2006)
Cutaneous gene therapy and DNA vaccination are potential applications of plasmid delivery methods where a gene for an antigen or a therapeutic protein is inserted in the plasmid and applied to the skin. However, the delivery of the DNA plasmid is a major challenge due to the unusual physicochemical properties of the DNA, the tissue and cellular barriers and expression difficulties. Even though the skin is the most accessible organ of the body and it is an ideal target for gene therapy, the delivery of plasmid DNA across the skin is very difficult due to the specific barrier function of the stratum corneum and the inconsistent transfection rate of keratinocytes and other epidermal cells. To date there is no gene delivery system that was shown to be optimal for cutaneous gene therapy. In order to develop an efficient non-viral delivery vehicle we need to design a system that provides the combined properties of effective DNA condensation, cutaneous permeation, cellular transfection and sufficiently sustained expression. This paper reviews the formulation approaches and delivery methods for DNA through the skin in the context of the barriers both at the tissue and cellular levels for both vaccine and gene therapy applications.
Keywords: Cutaneous Gene Therapy